# Pullback Group of Two Group Homomorphisms into a Group ## Problem 244

Let $G_1, G_1$, and $H$ be groups. Let $f_1: G_1 \to H$ and $f_2: G_2 \to H$ be group homomorphisms.
Define the subset $M$ of $G_1 \times G_2$ to be
$M=\{(a_1, a_2) \in G_1\times G_2 \mid f_1(a_1)=f_2(a_2)\}.$

Prove that $M$ is a subgroup of $G_1 \times G_2$. Add to solve later

## Proof.

### $M$ is closed under the group operation

Suppose that $(a_1, a_2), (b_1, b_2) \in M$.
By definition, we have
$f_1(a_1)=f_2(a_2) \text{ and } f_1(b_1)=f_2(b_2). \tag{*}$ The product of $(a_1, a_2)$ and $(b_1, b_2)$ is
$(a_1, a_2)\cdot (b_1, b_2)=(a_1b_1, a_2b_2).$

We want to prove that this is in $M$. To see this, note that we have
\begin{align*}
f_1(a_1b_1)&=f_1(a_1)f_1(b_1) && \text{($f_1$ is a homomorphism)}\\
&=f_2(a_2)f_2(b_2) && \text{(by (*))}\\
&=f_2(a_2b_2) && \text{($f_2$ is a homomorphism)}.
\end{align*}

Therefore we have obtained
$f_1(a_1b_1)=f_2(a_2b_2),$ and the product $(a_1b_1, a_2b_2)$ is in $M$ by definition.

### $M$ is closed under inverses

We next prove that if $(a_1, a_2)\in M$ then the inverse
$(a_1, a_2)^{-1}=(a_1^{-1}, a_2^{-1})$ is also in $M$.

Since $(a_1, a_2)\in M$, we have
$f_1(a_1)=f_2(a_2). \tag{**}$ Then we have
\begin{align*}
f_1(a_1^{-1})&=(f_1(a_1))^{-1} && \text{($f_1$ is a homomorphism)}\\
&=(f_2(a_2))^{-1} && \text{ (by (**))}\\
&=f_2(a_2^{-1}) && \text{($f_2$ is a homomorphism)}.
\end{align*}
Thus by definition the inverse $(a_1^{-1}, a_2^{-1})$ is in $M$.

Since $M$ is closed under the group operation and inverses, it is a subgroup of $G_1 \times G_2$.

## Comment.

In category theory, the subgroup $M$ in the problem is called a pullback of homomorphisms $f_1: G_1 \to H$ and $f_2: G_2 \to H$. Add to solve later

### More from my site

#### You may also like...

This site uses Akismet to reduce spam. Learn how your comment data is processed.

###### More in Group Theory ##### A Group Homomorphism is Injective if and only if Monic

Let $f:G\to G'$ be a group homomorphism. We say that $f$ is monic whenever we have $fg_1=fg_2$, where $g_1:K\to G$...

Close